1991
DOI: 10.1113/jphysiol.1991.sp018470
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for descending tonic inhibition specifically affecting sympathetic pathways to the kidney in rats.

Abstract: SUMMARY1. The present study investigated the possibility that pre-and postganglionic neurones innervating the kidney and spleen in rats are affected by descending inhibitory as well as descending excitatory influences. This hypothesis was tested by comparing the effects of cervical spinal cord transection to the effects of blockade of tonic activity of excitatory neurones in the rostral ventrolateral medulla (RVLM).2. Electrical discharge of multifibre postganglionic renal and splenic and preganglionic greater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…With regard to the sympathetic premotor nuclei, the critical role of the RVLM in the tonic and phasic control of RSNA has been clearly demonstrated in several species 16 . For example, bilateral inhibition of RVLM neurons causes virtually complete abolition of RSNA 17,18 . Similarly, the increase in RSNA reflexly evoked by activation of somatic nociceptive afferent fibres or peripheral chemoreceptors is abolished by blockade of glutamate receptors in the RVLM 16 .…”
Section: Overview Of the Organization Of Central Pathways Controllingmentioning
confidence: 99%
“…With regard to the sympathetic premotor nuclei, the critical role of the RVLM in the tonic and phasic control of RSNA has been clearly demonstrated in several species 16 . For example, bilateral inhibition of RVLM neurons causes virtually complete abolition of RSNA 17,18 . Similarly, the increase in RSNA reflexly evoked by activation of somatic nociceptive afferent fibres or peripheral chemoreceptors is abolished by blockade of glutamate receptors in the RVLM 16 .…”
Section: Overview Of the Organization Of Central Pathways Controllingmentioning
confidence: 99%
“…21 In this context, it has been reported that most spinal cord reflexes appear to be inhibited by supraspinal centers. 22 It is tempting to speculate that when the autonomic nervous system is challenged, as during orthostatic stress, partial loss of this complex regulation, as occurs in tetraplegics, might allow a greater expression of positive feedback mechanisms than could be fully integrated at the spinal level. 12,22 Removal of supraspinal inhibition during stress would correspond to the observation that nonbaroreflex sequences increased in response to HUT in tetraplegics.…”
Section: Legramante Et Al Neural Feedback Regulating Circulation In Hmentioning
confidence: 99%
“…22 It is tempting to speculate that when the autonomic nervous system is challenged, as during orthostatic stress, partial loss of this complex regulation, as occurs in tetraplegics, might allow a greater expression of positive feedback mechanisms than could be fully integrated at the spinal level. 12,22 Removal of supraspinal inhibition during stress would correspond to the observation that nonbaroreflex sequences increased in response to HUT in tetraplegics. This interpretation would fit well with the observation of a central neural occlusive interaction between simultaneous stimulations of sympathetic and parasympathetic cardiac afferents that limits opposing cardiovascular reflex responses.…”
Section: Legramante Et Al Neural Feedback Regulating Circulation In Hmentioning
confidence: 99%
“…HPA/SNS responses are coordinated in the spinal cord via supraspinal projections and by afferent feedback from the periphery to sympathetic preganglionic neurons (SPNs) (Hayes et al, 1991;Taylor and Weaver, 1993). SPNs found throughout the thoracic spinal cord (T3-13; (Strack et al, 1989;Cano et al, 2001) influence immune function through post-ganglionic noradrenergic projections to spleen (Wan et al, 1993) and adrenal cortex (Bloom et al, 1988;Engeland, 1998).…”
Section: Introductionmentioning
confidence: 99%